1978
DOI: 10.1079/bjn19780134
|View full text |Cite
|
Sign up to set email alerts
|

The accretion of copper and of zinc by the foetuses of prolific ewes

Abstract: 1. The amounts of copper and zinc in the foetuses of ewes carrying from one to four lambs were measured at different stages of gestation and estimates were made of the amounts of these metals in their livers.2. The accretion of Cu and Zn could be described by growth equations of the Gompertz form, from which could be derived estimates of the instantaneous and fractional rates of deposition of these metals in the foetal body.3. Between the 80th and 144th day of gestation the instantaneous rates of deposition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…5,51-53 A decline in fetal liver Zn concentration with age also has been described for sheep. 19,54,55 Although a negative interaction of Zn and Cu has been suggested to occur, fetal Zn and Cu were positively correlated in this and in the Canadian study. 14,15,24,25,34,43 O ur observed positive correlations between fetal size and fetal Zn and between fetal Zn and fetal Cu can be attributed to induction of fetal metallothionein.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…5,51-53 A decline in fetal liver Zn concentration with age also has been described for sheep. 19,54,55 Although a negative interaction of Zn and Cu has been suggested to occur, fetal Zn and Cu were positively correlated in this and in the Canadian study. 14,15,24,25,34,43 O ur observed positive correlations between fetal size and fetal Zn and between fetal Zn and fetal Cu can be attributed to induction of fetal metallothionein.…”
Section: Discussionmentioning
confidence: 58%
“…An increase in fetal Cu with fetal size has previously been reported for cattle and sheep. 14,15,54,55 In humans, fetal Cu concentrations reportedly increased or remained stable through gestation. 5,51,53 Bovine maternal and fetal Cu were positively correlated in this and previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…However, lambs can also be born with liver Cu stores that can sustain the animal for long periods in the face of inadequate intake. Williams et al (1978) have calculated that liver Cu could maintain the lamb for 2 weeks in the absence of dietary Cu. Further, since the absorption coefficient for Cu by the neonate approaches 1 and milk Cu is greatest in early lactation (Wiener et al, 1984), Cu deficiency is unlikely if the ewe is Cu adequate.…”
mentioning
confidence: 99%
“…Fetal liver Cu increased as fetal age increased and was less than to maternal Cu in early gestation and there was no differences between maternal and fetal liver Cu in late gestation, while fetal liver Cu was significantly higher than that of the maternal liver through gestation (Gonneratne and Christensen, 1989a), as well as Cu concentration was significantly increased in early gestation than that of late gestation in the fetal liver (Abdelrahman and Kincaid, 1993) and kidney while (Richards, 1999) found that in fetal kidney, Cu concentration did not change significantly with gestation. An increase in fetal Cu with fetal size has previously been reported for cattle and sheep (Gonneratne and Christensen, 1989a;Williams et al, 1978;Williams and Bremn, 1976). Numerous studies have shown significant correlations between fetal and maternal tissue copper concentration.…”
Section: Discussionmentioning
confidence: 92%